A putative design for the electromagnetic activation of split proteins for molecular and cellular manipulation - Grady, Connor J.; Castellanos Franco, E. Alejandro; Schossau, Jory; Ashbaugh, Ryan C.; Pelled, Galit; Gilad, Assaf A. (Frontiers in Bioengineering and Biotechnology, 2024)
The ability to manipulate cellular function using an external stimulus is a powerful strategy for studying complex biological phenomena. One approach to modulate the function of the cellular environment is split proteins. In this method, a biologically active protein or an enzyme is fragmented so that it reassembles only upon a specific stimulus. While many tools are available to induce these systems, nature has provided other mechanisms to expand the split protein toolbox. Here we show a novel method for reconstituting split proteins using magnetic stimulation. We have found that the Electromagnetic Perceptive Gene (EPG) changes conformation due to magnetic field stimulation. By fusing split fragments of a certain protein to both termini of the EPG, the fragments can be reassembled into a functional protein under magnetic stimulation due to conformational change. We show this effect with three separate split proteins; NanoLuc, APEX2, and Herpes Simplex Virus Type-1 Thymidine Kinase. Our results show for the first time, that reconstitution of split proteins can be achieved only with magnetic fields. We anticipate that this study will be a starting point for future magnetically inducible split protein designs for cellular perturbation and manipulation. With this technology, we can help to expand the toolbox of the split protein platform and allow better elucidation of complex biological systems.